Design of a resonant slow extraction from low-emittance electron booster rings using transverse resonance island buckets - E. C. Cortés García; I. V. Agapov; W. Hillert (Physical Review Accelerators and Beams)
In this contribution, we present the design of a resonant slow extraction based on the radio-frequency knockout (rf-KO) scheme, where we make use of the transverse resonance islands bucket (TRIB) optics. The generation of the TRIB optics is presented in two example lattices, which are considered for the potential upgrade of the current booster at DESY. The slow extraction studies are motivated to potentially supply high energy electron beams to the high energy physics beamline users. Simulations show an extraction efficiency in excess of 90% with a septum blade thickness of 100  μm.